Transplantation Amid a Pandemic: The Fall and Rise of Kidney Transplantation in the United States - Shivani S. Bisen, BA; Laura B. Zeiser, ScM; Brian Boyarsky, MD, PhD; William Werbel, MD; Jon Snyder, PhD; Jacqueline Garonzik-Wang, MD, PhD; Macey L. Levan, JD, PhD; Dorry L. Segev, MD, PhD; Allan B. Massie, PhD, MHS (Transplantation Direct, 2023)
Background. Following the outbreak of coronavirus disease 2019 (COVID-19) in the United States, the number of kidney waitlist additions and living-donor and deceased-donor kidney transplants (LDKT/DDKT) decreased substantially but began recovering within a few months. Since then, there have been several additional waves of infection, most notably, the Delta and Omicron surges beginning in August and December 2021, respectively. Methods. Using SRTR data, we compared observed waitlist registrations, waitlist mortality, waitlist removal due to deteriorating condition, LDKT, and DDKT over 5 distinct pandemic periods to expected events based on calculations from preepidemic data while accounting for seasonality and secular trends. Results. Although the number of daily waitlist additions has been increasing since May 2020, the size of the active waitlist has consistently declined, reaching a minimum of 52 556 on February 27, 2022. The recent Omicron surge knocked LDKT from 25% below baseline (incidence rate ratio [IRR] = 0.690.750.81) during the Delta wave to 38% below baseline (IRR = 0.580.620.67). DDKT, however, was less affected by the Omicron wave (IRR = 0.850.890.93 and 0.880.920.96 during the Delta and Omicron waves, respectively). Waitlist death decreased from 56% above baseline (IRR = 1.431.561.70) during Delta to 41% above baseline during Omicron, whereas waitlist removal due to deteriorating condition remained at baseline/expected levels during the Delta wave (IRR = 0.931.021.12) and the Omicron wave (IRR = 0.991.071.16). Conclusions. Despite exceptionally high COVID-19 incidence during the Omicron wave, the transplant system responded similarly to prior waves that imposed a lesser disease burden, demonstrating the transplant system’s growing adaptations and resilience to this now endemic disease.